(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper breakdowns the measurement issues in education accomplishment, and coordination of education objectives and targets, in the connection of human development in India. Measurement issues are recognized by (a) decision of indicators and variables and (b) data utilized within estimation/projection/computation of indicators and variables in the global human development reports (Hdrs) and in India’s national and sub-national Hdrs. This analysis establishes the non-likeness of measurement of the education accomplishment by indicators and variables, and shows a case for mix of education objectives and targets between global, national and sub-national levels. Policy suggestions and goals from these breakdowns of the Indian experiences offer lessons for measurement of education accomplishment in creating countries.